The Influence of Service Quality on Brimo User Satisfaction with Convenience as an Intervening Variable on Management Students of Makassar State University - Sahabuddin, Romansyah; Arif, Hery Maulana; Ulfiyanah, Nirma; Mahrip, Shofia Ghaisani; Khaliq, Muhammad Fathul; Baharuddin, Baharuddin (International Journal on Advanced Science, Education, and Religion, 2024)
This study aims to examine the impact of service quality on BRImo user satisfaction, with convenience as an intervening variable, both partially and simultaneously. The research sample consisted of 125 management students of Makassar State University, and the analysis was conducted using the Partial Least Square (PLS) method with the help of SmartPLS4 software. The results of the study indicate that partially, service quality has a positive and significant effect on user satisfaction. In addition, service quality also has a positive and significant effect on convenience. This convenience, in turn, has a positive and significant effect on user satisfaction. Service quality also has a positive and significant effect on user satisfaction through convenience as an intervening variable in the use of BRImo.